2014
DOI: 10.4103/0377-4929.134708
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Staphylococcus hominis subsp. novobiosepticus causing septicemia in patients with malignancy

Abstract: A new subspecies of Staphylococcus hominis described by Kloos et al. in 1998 and named S. hominis subsp. novobiosepticus (SHN) has been implicated in nosocomial outbreaks. Multidrug resistance, including resistance to novobiocin and oxacillin, is a particularly important feature of SHN. In our institute, we encountered 13 cases of S. hominis subsp. hominis in cancer patients with septicemia, of which seven were methicillin resistant. The isolates were identified by VITEK ® 2 compact automated system, using GP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…4). Various sub-species of this species had been implicated for nosocomial outbreaks causing bloodstream infections in patients with underlying malignancies [27].…”
Section: Discussionmentioning
confidence: 99%
“…4). Various sub-species of this species had been implicated for nosocomial outbreaks causing bloodstream infections in patients with underlying malignancies [27].…”
Section: Discussionmentioning
confidence: 99%
“…S. hominis isolates display a lower virulence than S. haemolyticus and have been recognized, less frequently, as significant human pathogens. However, there are reports indicating that S. hominis can be responsible for nosocomial outbreaks (Chaves et al 2005 ; d’Azevedo et al 2008 ; Palazzo et al 2008 ; Sorlozano et al 2010 ; Ruiz de Gopegui et al 2011 ; Roy et al 2014 ). Nevertheless, there is limited information on their resistance to antibiotics, especially to macrolides, lincosamides and streptogramin B.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that most species identified in this study are typically found in soil, seawater, sediments, and human skin or gut microbiota, and only a few species have been recently reported in the literature to cause rare infections in people, such as Corynebacterium sanguinis (Jaén‐Luchoro et al, 2020 ), Dermabacter jinjuensis (Cho et al, 2018 ), Dermacoccus nishinomiyaensis (Joron et al, 2019 ; Ogbac, 2021 ), Enterococcus faecalis (Li et al, 2020 ), Rhodococcus corynebacterioides (Kitamura et al, 2012 ), Brachybacterium paraconglomeratum (Murata et al, 2020 ), Streptococcus agalactiae (Ya'qoub et al, 2018 ), Micrococcus luteus (Zhu et al, 2021 ) and finally, more commonly, Staphylococcus hominis (Ahmed et al, 2017 ; Jeon et al, 2022 ; Muraki et al, 2022 ; Uddin et al, 2022 ; Vasconcellos et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, S. hominis has been reported as an opportunistic pathogenic bacterium typically found in the human oropharynx and URT (Otto, 2010 ; Szczuka et al, 2018 ); present in the blood of immunocompromised patients with bacteremia, septicemia, endophthalmitis, and endocarditis (Ahmed et al, 2017 ; Jeon et al, 2022 ; Muraki et al, 2022 ; Uddin et al, 2022 ; Vasconcellos et al, 2022 ), and often it can form biofilms on medical devices (Villarreal‐Salazar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%